Maintaining food and nutrition security in Myanmar during the COVID-19 crisis: Lessons from India’s lockdown - Researchers of the International Food Policy Research Institute and Michigan State University; Headey, Derek D. (International Food Policy Research Institute, 2020)
The recent sudden imposition of a stringent 21-day lockdown in India in the face of the COVID-19 pandemic has adversely affected the food security of many vulnerable Indians. These impacts highlight the many challenges that this kind of anti-COVID intervention can pose in other settings where the labor force is mostly informally employed with poor job security and low wages, and where the agri-food systems is similarly informal with widespread use of open-air markets. Myanmar is such a setting. India’s chastening experience with food security during its lockdown suggests the following actions would be imperative for maintaining food security in Myanmar: • Allow the free movement of all goods. A stable and reliable agri-food system requires free movements of a wide range of food products (including micronutrient-rich fruits, vegetables and animal-sourced foods) as well as essential non-food goods. • Monitor food markets and agricultural value chains as closely as possible to address problems when they do arise. • Reduce risk of COVID-19 contagion by improving hygiene in Myanmar’s food markets. • Issue clear directives to police, military, and local authorities not to impede the movement of goods. The Government of Myanmar should learn from the mistakes made in India and other developing countries. We must recognize that basic food and nutrition security must be maintained at all times through this complex health and socioeconomic crisis.